Phenotyping of an in vitro model of ischemic penumbra by iTRAQ-based shotgun quantitative proteomics - Tam, James P. (2014)
Cerebral ischemia is a major cause of death and long-term disability worldwide. Ischemic penumbra, the electrically silent but metabolically viable perifocal brain tissue, is the target for the much elusive stroke therapy. To characterize the molecular events of the dynamic penumbra, we applied an iTRAQ-based shotgun proteomic approach in an in vitro neuronal model, using the rat B104 neuroblastoma cell line. Various functional and cytometric assays were performed to establish the relevant time-point and conditions for ischemia to recapitulate the pathology of the penumbra. Two replicate iTRAQ experiments identified 1796 and 1566 proteins, respectively (≤1.0% false discovery rate). Mining of proteomic data indicated the up-regulation of proteins involved in ammoniagenesis, antiapoptotic, anti-inflammatory and mitochondrial heat shock response and down-regulation of proteins pertaining to antioxidative defense and protein metabolism. Additionally, many proteins (for instance, park7 and VAP-A) involved in the chronic neurological disorders (such as Alzheimer’s disease, Parkinson’s disease or Bipolar disorder) were also regulated in this model of acute neuronal injury. Our results also provide preliminary evidence about the presence of a relative glucose paradox under in vitro conditions indicating possible application of this cell system to study the mechanisms of transient protection induced by concomitant glucose deprivation under hypoxia. In conclusion, our study shows the potential application of iTRAQ-based quantitative proteomics for the elucidation of pathophysiology and the discovery of novel therapeutic targets in the field of neuroproteomics.